Blood-letting therapy for the common cold: A protocol for a systematic review of controlled trials. Issue 51 (December 2017) - Lee, Ju Ah; Hong, Minna; Lee, Myeong Soo; Yoon, Seong Hoon; Choi, Jun-Yong
Abstract: Background: Many people experience the common cold, but there is currently no special treatment. For this reason, complementary and alternative medicine (CAM) therapies are used to improve the symptoms of the common cold. Blood-letting therapy (BL) is a CAM therapy that has been used for over 2000 years to treat various diseases. However, few studies have provided evidence for the efficacy and safety of BL for the common cold. This study aims to assess the effectiveness and safety of BL for the common cold. Methods and analysis: A total of 11 databases will be searched for studies conducted through June 2017. We will include randomized controlled trials assessing BL for the common cold. All randomized controlled trials on BL or related interventions will be included. Risk of bias will be assessed using the Cochrane Risk of Bias Assessment Tool, while confidence in the accumulated evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation instrument. Ethics and dissemination: This systematic review will be published in a peer-reviewed journal and will also be disseminated electronically and in print. The review will be updated to inform and guide healthcare practices.